Assessment of Factors Affecting Discharge Planning Implementation in Margaret Marquart Catholic Hospital - Azari, A.S. (University of Ghana, 2017)
Discharge from a hospital does not mark the end of care or indicate cure of disease thus care must continue at home in order to maximize health gains. Discharge planning implementation (DPI) ensures conterminous care after discharge and understanding the factors that affect clinical staff’s compliance to DPI may improve clinical practice. This study aimed to assess the factors affecting DPI compliance in Margaret Marquart Catholic Hospital. Method In this study, 112 clinical staff and 281 discharged adult patients/relatives were purposively sampled and interviewed at enclosed settings. Structured questionnaires and a data extraction tool were used to collect data from participants and documentary review. The mean/median of each variable was used as a dividing line to split the variables into positive and negative scores. Chi square test was performed for an association and logistic regression for the strength of association. Results The majority (57%) of the staff complied to discharge planning implementation but few patients, (43%), received DPI. Of all the factors, hospital system (OR =3.57, p=0.02, 95%CI:0.20,2.37), the absence of discharge policy and patient health literacy affected DPI compliance. Conclusion: Improving staff compliance requires coordination of system-wide discharge policy implemented by hospital managers demonstrating DPI as a priority to serve patients/families with regard and willingness to wait for discharge planning execution.
Keywords: association; implementation; planning; coordination; participants